PENGARUH KUALITAS SISTEM DAN KUALITAS INFORMASI TERHADAP KEPUASAN PENGGUNA SISTEM INFORMASI AKUNTANSI (STUDI KASUS SISTEM IPOS/INTEGRATED POSTAL OPERATIONS SYSTEM PADA PT. POS INDONESIA CABANG KOTA PEMATANGSIANTAR) - Ade Mitha Olivia Tambunan; Jonny Siagian; Melinda Malau (Buletin Ekonomi, 2023)
are unable to keep up with the changing dynamics of the information technology industry must be ready to fall behind their rivals. The issue that needs to be addressed in this study is the connection between system quality and information quality and user satisfaction. This study was carried out at PT. POS Indonesia's City Branch at Pematangsiantar. The goal of this study was to find out how user satisfaction is affected by system and information quality. Purposive sampling was used to collect 35 samples from 57 people in total for this study. Multiple linear regression analysis was used in this study's tests. The study's final findings are as follows: 1) User satisfaction is positively correlated with system quality, suggesting that as system quality improves, so will the number of accounting information system users. 2) The positive impact of information quality on user satisfaction suggests that, if information is of high quality, it will also have a positive impact on user satisfaction. 3) User satisfaction is influenced simultaneously by the quality of the system and the quality of the information. This means that users of the accounting information system will be more satisfied with the IPOS system if the quality of the system and the quality of the information are designed appropriately. Keywords: Quality, User Satisfaction, and IPO